(3EYQGH GdbQBfs - (3GdRLGL , EHQGgje Hf GdSQj Hf Sgd, CHhESMGb,J (B311 (3g` s
(3ChdgG (B:s
(3bhdg (B" (3hdhdG EP ONdJ LfJc (B" (3ef ShQI Gdcga s
(3BNQgG (B:s
(3ef EYQGH bhdg JYGdi ef ShQI GdaQbGf (B:" (3aOeQfGge JOejQG (B" (3jYfi Hg aQYhf hbheg hGdPjf eSNhG bQOI hNfGRjQ Je GdLRA jJdhg bhdg (B" (3hbhe fhM deG cPHhG GdQSd CZQbfGge (B" s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B33s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(333(3b(B) s
Keywords: (3GdfMhs